Beta defensin 3 enhances ovarian granulosa cell proliferation and migration via ERK1/2 pathway in vitro†. Issue 4 (16th November 2018) - Liu, Canying; Pan, Bo; Yang, Lu; Wang, Bingyun; Li, Julang
Abstract: Antimicrobial peptides (AMPs) are regarded as host defense peptides that possess bactericidal activity as well as immunomodulatory function. However, the role of AMP in the mammalian ovary is unknown. In the present study, porcine granulosa cells were utilized in a cell model to study the role of porcine beta defensin 2 (pBD2; pDEFB4B) and 3 (pBD3; pDEFB103A) during ovarian follicular development. Granulosa cells were cultured in the absence and presence of 1, 10, and 50 μg/ml of pDEFB4B or pDEFB103A. After 24 h of treatment, pDEFB103A but not pDEFB4B stimulated granulosa cell proliferation in a concentration-dependent manner ( P < 0.05). This effect was dependent on the stage of follicular development. In addition, transwell cell migration assay showed that in the presence of pDEFB103A (10 μg/ml), a 2.5-fold increase in cell migration was achieved. Furthermore, further study revealed that pDEFB103A increased the mRNA levels of cyclin D1 ( CCND1 ) and proliferating cell nuclear antigen ( PCNA ), both associated with cell proliferation. To study the potential pathway involved in pDEFB103A-induced cell proliferation and migration, western blots were performed. It was found that pDEFB103A significantly increased the phosphorylated-ERK1/2 to nonphosphorylated ratio. Moreover, pretreatment with the U0126, a specific ERK1/2 phosphorylation inhibitor, suppressed PDEFB103A inducing GCs ERK1/2 phosphorylation, as well as proliferation and migration, suggesting that PDEFB103A may act via activating the ERK1/2 pathway. Furthermore, using a signal transduction pathway Elk-1 trans-reporting system, the activation of ERK1/2 pathway by PDEFB103A was further confirmed. Our data suggest that AMP may play a physiological role in the mammalian ovary. Abstract : Beta defensin 3, regarded as host defense peptide which possess bactericidal activity and immunomodulatory function, enhanced granulosa cell migration and proliferation via its activation of the ERK1/2 pathway.